Delayed presentation of extensor pollicis longus tendon injury treated using extensor indicis proprius tendon transfer - Ghelani, Nilesh B.; Shah, Sankit; B. P., Sunmathi; Patel, Samir (International Surgery Journal, 2019)
Spontaneous closed rupture of EPL tendon are frequently associated with rheumatoid arthritis, Colles fracture, sports related injury. In cases of delayed presentation direct tendon repair is not feasible and a tendon transfer is usually recommended. In this study we evaluated the results of extensor indicis proprius (EIP) to extensor pollicis longus (EPL) transfers for EPL ruptures. Four patients, (two male and two females); mean age 32 years (range 20 to 45 years) with EPL tendon rupture underwent EIP to EPL tendon transfer. The mean duration from rupture to surgery was 4.5 weeks (range 4 to 6 weeks). Range of motion of the metacarpophalangeal (MCP), interphalangeal joints (IP) of the thumb and index finger of the operated side was compared with the normal side. The results were scored using geldmacher scheme, for the thumb four functions were scored, the radial abduction angle, the elevation deficit, the opposition distance and flexion extension deficit of MP and IP joints. The mean follow-up period was 5 months. All the four patients were able extend the thumb at MCP joint and oppose the thumb to the MCP of little finger after mean follow up of 5 months. Based on the questionnaire, the results of tendon transfer scored by three (75%) patients was excellent and by one (25%) patient was good. Independent extension of the index finger of operated hand was possible in all 4 patients. The procedure of EIP to EPL tendon transfer provides excellent result for extension of thumb. It is a safe procedure.